Pelatihan Program Efisiensi Pengembangan Perangkat Pembelajaran dengan Artificial Intelligence (AI) untuk Guru Matematika SMP di Kabupaten Maros - Arwadi, Fajar; Hamda, Hamda; Asmaun, Asmaun; Hamid, Abdurahman (Jurusan Matematika FMIPA UNM, 2025)
This community service program conducted in Maros Regency aims to assist mathematics teachers, especially junior high school teachers, in developing learning tools with the help of artificial intelligence. The method of implementation of this activity is carried out by providing materials, mentoring accompanied by training and facilitating participants to develop learning with artificial intelligence. This activity was carried out at SMP Negeri 1 Maros, Maros Regency, South Sulawesi Province. Participants in this activity were junior high school teachers (SMP) in Maros Regency who are members of the MGMP SMP Maros. The results obtained in this activity show that the level of knowledge and understanding in developing teaching tools with artificial intelligence of participants after participating in the training has increased. In addition, participants are also able to use artificial intelligence applications such as Canva Magic AI to make their teaching tools more efficient, interesting and innovative. The response given by the participants at the end of the activity was also very enthusiastic, as evidenced by the results of the satisfaction questionnaire given.